Targeting Adrenomedullin in Oncology: A Feasible Strategy With Potential as Much More Than an Alternative Anti-Angiogenic Therapy - Vázquez, Ramiro; Riveiro, Maria E.; Berenguer-Daizé, Caroline; O’Kane, Anthony; Gormley, Julie; Touzelet, Olivier; Rezai, Keyvan; Bekradda, Mohamed; Ouafik, L’Houcine (Frontiers in Oncology, 2021)
The development, maintenance and metastasis of solid tumors are highly dependent on the formation of blood and lymphatic vessels from preexisting ones through a series of processes that are respectively known as angiogenesis and lymphangiogenesis. Both are mediated by specific growth-stimulating molecules, such as the vascular endothelial growth factor (VEGF) and adrenomedullin (AM), secreted by diverse cell types which involve not only the cancerogenic ones, but also those constituting the tumor stroma (i.e. macrophages, pericytes, fibroblasts and endothelial cells). In this sense, anti-angiogenic therapy represents a clinically-validated strategy in oncology. Current therapeutic approaches, however, are mainly based on VEGF-targeting agents. Unfortunately, these treatments are usually limited by toxicity and/or tumor-acquired resistance. On the other hand, AM is a ubiquitous peptide hormone mainly secreted in the endothelium with an important involvement in blood vessel development and cardiovascular homeostasis. In this review, we will introduce the state of the art in terms of AM physiology while putting a special focus on its pro-tumorigenic role. A large amount of research has evidenced AM overexpression in a vast majority of solid tumors and the correlation between AM levels and disease stage, progression and/or vascular density. The analysis presented here indicates that the involvement of AM in the pathogenesis of cancer is given by 1) directly promoting cell proliferation and survival; 2) favoring vascularization and the subsequent supply of nutrients and oxygen to the tumor; 3) and/or altering the cell phenotype into a more aggressive one. Furthermore, we have performed a deep scrutiny of the pathophysiological prominence of each of the AM receptors (AM1 and AM2) in different cancers, being highlighted their differential locations and functions as well as regulatory mechanism. From the therapeutic point of view, we summarize here an exhaustive series of preclinical studies showing a reduction of tumor angiogenesis, metastasis and growth upon the treatment with AM-neutralizing antibodies, AM receptor antagonists, or AM receptor interference, suggesting anti-AM therapy as a promising strategy to be explore in oncology, not only as an anti-angiogenic alternative in the context of VEGF-acquired resistance, but also as a potential anti-metastatic approach.